Four Decades of Bacillus Biofertilizers: Advances and Future Prospects in Agriculture - Xinmai Wu; Yan Liu; Baolei Jia; Lili Tao; Han Li; Jingbang Wang; Ziqi Yuan; Xiaobao Sun; Yanlai Yao (Microorganisms)
Over the past four decades, Bacillus biofertilizers, which are microbial formulations based on Bacillus species, have significantly contributed to sustainable agriculture by enhancing crop growth, improving soil health, and reducing the dependency on chemical fertilizers. Bacillus species, particularly known for their ability to promote plant growth, fix nitrogen, solubilize phosphorus, and produce growth-promoting substances such as phytohormones and antibiotics, have emerged as key players in the development of eco-friendly agricultural solutions. This research utilizes bibliometric analysis based on 3,242 documents sourced from the Web of Science database to map the development, key contributions, and innovation within the field from 1985 to 2023. This study identifies exponential growth in research output, particularly from 2003 onwards, indicating a robust interest and expanding research base predominantly in China, India, and the United States. We segmented the research timeline into three distinct phases, each marked by varying growth rates and research foci. This paper presents novel insights into the geographical and institutional distributions of research, highlighting the predominant role of developing countries in advancing Bacillus-based technologies. Key research hotspots have evolved from basic applications to complex interactions involving synthetic microbial communities and advanced multi-omics techniques. Our findings demonstrate a trend towards more strategic and technologically integrated approaches to developing Bacillus biofertilizers, reflecting broader shifts towards more sustainable agricultural systems. This study not only charts historical progress, but also proposes future research trajectories aimed at enhancing the application and effectiveness of microbial fertilizers across diverse ecosystems.